Decision‐making for older patients by Australian and New Zealand doctors with Advance Care Directives: a vignette‐based study. Issue 9 (10th September 2019) - Mitropoulos, Joanna; Austin, Nicole; Hunter, Peter; Cairney, Helena; Parikh, Seema
Abstract: Background: Little is known about doctors' decision‐making patterns when using Advance Care Directives (ACDs), particularly for older patients in Australia and New Zealand. Aims: To determine the level of agreement among Australian and New Zealand doctors' decisions when using ACDs to guide treatment decisions for older patients. To evaluate factors that may affect decision‐making including doctors' demographics, vignette complexity and Advance Care Directive (ACD) content. Methods: In December 2016–January 2017, a survey was distributed to doctors working within one tertiary hospital network in Melbourne and to doctors registered with the Australian and New Zealand Society of Geriatric Medicine. The survey comprised of three vignettes (1, 2, 3) presented with deidentified versions of genuine ACDs (A and B) volunteered by community members via a tertiary hospital ACD service. Results: Five hundred and sixty doctors submitted completed surveys. The level of agreement between doctors when using ACDs varied by vignette complexity, ACD content, doctor speciality ( P = 0.006 vignette 1 ACD A, P = 0.04 vignette 1 ACD B, P = 0.04 vignette 2 ACD A, P = 0.04 vignette 3 ACD B) and doctor seniority ( P = 0.04 vignette 1 ACD A, P < 0.0001 vignette 2 ACD A). Australian and New Zealand doctors are infrequently exposed to ACDs in their work, 30% did not know the legal status of ACDs and majority of the cohort requested more education on ACDs. Conclusion: Despite the presence of an ACD, the level of agreement on treatment decisions for older patients when using ACDs varies by vignette complexity, ACD content, speciality and seniority of doctors.